Can virtue epistemology solve the Gettier problem? - Kaluziński, Bartosz (Hybris, 2015)
The aim of this paper is to investigate if ideas developed by philosophers representing the current called Virtue Epistemology are able to resolve the Gettier problem. First of all, I am going to remind what classical concept of knowledge as justified true belief consists in, then I present co-called Gettier cases that are counterexamples to the classical idea of knowledge. Then I investigate how the idea of evaluating beliefs formulated by Ernest Sosa is able to deal with hard cases made by Gettier, but also Chisholm and Goldman. I argue that Sosa’s conception could be viewed as satisfactory analysis of knowledge, if we slightly modify it to accommodate Goldman’s case.